Mild-to-moderate symptoms during the first year of antiretroviral therapy worsen quality of life in HIV-infected individuals. - Mannheimer, Sharon B; Wold, Nicholas; Gardner, Edward M; Telzak, Edward E; Huppler Hullsiek, Katherine; Chesney, Margaret; Wu, Albert W; MacArthur, Rodger D; Matts, John; Friedland, Gerald (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2008)
Symptoms and quality of life were assessed among human immunodeficiency virus (HIV)-infected individuals initiating their first course of antiretroviral therapy. Symptoms, which were mostly mild or moderate, were common in the first year and significantly affected the patients' quality of life. Quality of life was inversely related to the number of symptoms and in the change in the number of symptoms from baseline.
Keywords: Adult; Anti-HIV Agents; Drug Therapy, Combination; Female; HIV Infections; HIV Protease Inhibitors; HIV-1; Humans; Male; Middle Aged; Quality of Life; Reverse Transcriptase Inhibitors; Severity of Illness Index; Treatment Outcome